Algorithmic governance, code as law, and the blockchain common: Power relations in the blockchain-based society - Kozak, Krystyna (Frontiers in Blockchain, 2023)
"Code is law" became a buzz term in Web3 and blockchain reality. Despite the term being already used much earlier by Lawrence Lessig in the year 2000 in his book titled "Code and Other Laws of Cyberspace", when the internet and Web2 were emerging, the rise of smart contracts and complex algorithmic power made the term genuinely resonate with the (idealised) Web3 reality. The entrainment of technological solutionism in the brains of members of society gives an impression that a world governed by algorithms will be a fairer one. The proponents of blockchain and web3 technology argue that with a DAO-governed, decentralised society, problems of biased algorithmic governance are solved as power and decision-making are decentralised, and members use their governance tokens to collectively decide on the law encoded in the smart contracts that are the ultimate law enforcement apparatus. This paper is based on decoding this promise and using Althusser's model of a state apparatus to show how the power relations changed in Web2 and Web3 realities. The power relations in the blockchain society are researched. to show that in Web3, "code is law" society, there will be power struggles and opposition on a vertical and horizontal level on the ideological and repressive apparatuses levels(according to Althusser's (1970) model). Overall, the paper argues that blockchain-based "code is law" reality does not solve the issue of unequal power relations within societies but only as any technological revolution shifts the power relations and power struggles between existing and new actors.